Students' Experiences of Undergraduate Dissertation Supervision - Roberts, Lynne D.; Seaman, Kristen (Frontiers in Education, 2018)
Increasingly, students completing undergraduate dissertations in Australia are expected by their supervisors to produce publishable research. Despite this, limited resources are available for supervisors of undergraduate dissertation students on how best to supervise students towards this aim. Building on our previous research on the perspectives of supervisors and dissertation coordinators of what constitutes good undergraduate dissertation supervision we present here the findings on student perspectives of good supervision. Twenty-five students (seventeen students who were currently completing an undergraduate dissertation and eight who had recently completed an undergraduate dissertation) were interviewed about their experiences in being supervised. A critical incident methodology was used to invite students to reflect on times when supervision had gone well, and times when it had not. Interviews were recorded and transcribed and analyzed using thematic analysis. Key themes to emerge were that students viewed ‘good’ supervisors as those that were supportive and empowering, directed learning, and whose style and interests aligned with those of the students. Issues in supervision related to lack of clarity and inconsistencies, perceived power imbalances between students and supervisors, and perceived inequities in the amount of supervision provided across students. Whilst the publication of undergraduate research is a worthy aim, the pressure to publish for some students resulted in feelings of inadequacy and perceptions of supervisors losing interest when findings were not deemed publishable.